Meaning of luxury in hospitality: An analysis of multiple destinations - Correia, A.; Reis, H.; Moro, S.; Kozak, M. (Journal of Hospitality and Tourism Management, 2022)
Over the recent years, the status of luxury has been a fast-growing niche market (Alnawas & Hemsley-Brown, 2019; Chang, Ko, & Leite, 2016; Lo & Yeung, 2020; Yang & Matilla, 2016), contributing to enhancing its status of tourism to a superior commodity, usually labelled as luxuries. This promise of status enhancement has attracted managers to enter the luxury segment, thus conferring to their resorts (Yin Chu, Liang Tang, & Yi Luo, 2016; Walls, Okumus, Wang, & Joon-Wuk Kwun, 2011). The hospitality industry exerts efforts to have high involvement services, rich physical environments and professional services that support the prices (Knutson, Stevens, Patton, & Thompson, 1993; Seyfi, Hall, & Rasoolimanesh, 2020; Titz, 2007). However, tourists in luxury hotels are not expected to have only functional benefits since they also look for value experiential services (Alnawas & Hemsley-Brown, 2019; Cetin & Walls, 2016; Chaney, Lunardo, & Mencarelli, 2018; Walls, Okumus, Wang, & Kwun, 2011).